2013
DOI: 10.4236/jhrss.2013.13007
|View full text |Cite
|
Sign up to set email alerts
|

Work-Family Conflict Influences on Female’s Career Development through Career Expectation

Abstract: Nowadays, women are still underrepresented in the higher positions in most organizations. Some crucial questions are whether family responsibilities affect female career development and career expectation influences the relationship between work and family conflict and career development of women or not. Through surveying the female teachers in Lin Yi University and Shandong Medical College, this article wants to know the correct relationship among work and family conflict, career expectations and career devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…This shows that career development is high even though in the presence of strong work-family conflict. This result supports previous research conducted by (Wang & Cho, 2013) which stated that work-family conflict negatively effects career development that resulted in low career development for women. The other way that education and career of a woman is significantly influenced by social pressure (Marks & Houston, 2002).…”
Section: Effect Of Work-family Conflict On Career Developmentsupporting
confidence: 91%
“…This shows that career development is high even though in the presence of strong work-family conflict. This result supports previous research conducted by (Wang & Cho, 2013) which stated that work-family conflict negatively effects career development that resulted in low career development for women. The other way that education and career of a woman is significantly influenced by social pressure (Marks & Houston, 2002).…”
Section: Effect Of Work-family Conflict On Career Developmentsupporting
confidence: 91%
“…As these results demonstrate, however, traditional gender norms are still in play. These dual expectations may result in conflict between family and work, as demonstrated in other studies which document conflict between family and work [22] and may have a negative influence on career development [23].…”
Section: Discussionmentioning
confidence: 86%
“…As past studies have shown, the influences and expectations of family play a key role in career development (Fouad et al, 2010). For instance, by investigating the relationship among work and family conflict, CEs, and career development for Chinese women, Wang and Cho (2013) argued that "women face high work-family conflict, influencing their career expectation and hindering career development" (p. 49).…”
Section: Ce and Career Successmentioning
confidence: 99%